دور رأس مال المخاطر في تحقيق الميزة التنافسية للمؤسسات الصغيرة و المتوسطة من خلال إستدامتها - حديدي آدم; براهيمي فائزة (جامعة الوادي University of Eloued, 2024)
This paper aims at determining the role of venture Capital in enhancing the competitive advantage of small and medium enterprises through its sustainability, and for that the questionnaire was used as a tool for scientific research by surveying a sample of workers in small and medium enterprises, using the equations regression depending on the Baron and Kenny model , As a tool to test the hypotheses of the study by using the statistical program Spss. The study reached a set of results, the most important of which is that the venture Capital is an innovative means of financing institutions and that relying on it will enhance the of the competitive advantage of small and medium enterprises through its sustainability and in the end, we came out with a set of recommendations.
The role of risk capital in achieving the competitive advantage of small and medium enterprises through its sustainability
Keywords: رأس مال المخاطر; الميزة التنافسية; المؤسسات الصغيرة و المتوسطة; إستدامة المؤسسات; نموذج برون و كيني